The Brisbane Breast Bank. (6th February 2018) - McCart Reed, Amy E.; Saunus, Jodi M.; Ferguson, Kaltin; Niland, Colleen; Simpson, Peter T.; Lakhani, Sunil R.
The Brisbane Breast Bank (BBB) was established in 2005 with a view to collecting surplus tissue from every breast surgery patient at the Royal Brisbane and Women's Hospital. This not-for-profit biobank provides resources on a collaborative basis, supporting local, national and international studies. The resource prides itself on its comprehensive clinico-pathology sample annotation. Since its inception, the remit of the BBB has expanded to the prospective collection of serial blood samples from patients at high risk of recurrence, and the collection of blood and tumour tissue from metastatic patients.